The Effect of the use of E-Learning Teaching Physiology in the Academic Achievement of Students of the Technical Medical Institute - Mayad Nazim Rashid (Institute of Medico-legal Publications Pvt Ltd, 2020)
Physiology is an important science that is taught at the Technical Medical Institute, where it is taught in most sections and branches, and to know the extent of the student’s understanding and mental abilities by the use of modern technology, and learning may be an immediate or simultaneous learning in the classroom or outside. E-learning is characterized by ease and modification of information provided and increases the possibility of communication to exchange views, experiences and perspectives between students and teachers and overcome the problem of the number of students with narrow classrooms. It is also successful for the “traditional education” that exists at the institute, where it constitutes the collective presence of students and promotes joint work among them. The present research aims to identify the effect of using an e-learning by teaching physiology in the academic achievement of the students of the Technical Medical Institute. They were divided into two groups, the first experimental and the second by twenty students for each group, one of the experimental group that studied e-learning method and the second control, which studied by lecture method.